PENGARUH DIGITAL MARKETING, BRAND IMAGE, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK MS GLOW - Jayanti, Esih; Daryani, Daryani; Sudiyono, Sudiyono (JURNAL EKONOMI, 2024)
The Influence of Digital Marketing, Brand Image, and Product Quality on Purchasing Decisions For MS Glow Products in Wanareja District. This study aims to examine the effect of digital marketing (X1), brand image (X2) and product quality (X3) on purchasing decisions (Y) for MS Glow products. The sample in this study was 117 respondents using the Lemeshow formula. Data collection techniques were carried out by distributing questionnaires. Analysis prerequisite tests included normality tests, linearty test, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. data with multiple linear regression. Statistical tests using the t test, F test, as well as the R2 test, and the classical assumption test. The results showed that (1) digital marketing has a significant effect on purchasing decisions for MS Glow products: ) brand image has a significant effect on purchasing decisions for MS products Glow: (3) Product quality has a significant effect on purchasing decisions for MS Glow products; (4) digital marketing, brand image, and product quality simultaneously have a significant effect onpurchasing decisions for MS Glow products.